2002
DOI: 10.1051/0004-6361:20020383
|View full text |Cite
|
Sign up to set email alerts
|

The role of magnetic helicity transport in nonlinear galactic dynamos

Abstract: Abstract. We consider the magnetic helicity balance for the galactic dynamo in the framework of the local dynamo problem, as well as in the no-z model (which includes explicitly the radial distribution of the magnetic fields). When calculating the magnetic helicity balance we take into account the redistribution of the small-scale and large-scale magnetic fields between the magnetic helicities, as well as magnetic helicity transport and diffusion due to smallscale turbulence. We demonstrate that the magnetic h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
135
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(143 citation statements)
references
References 25 publications
7
135
1
Order By: Relevance
“…Kleeorin et al (2000) suggested that a nonlinear galactic dynamo governed by a consistently derived equation for magnetic helicity results in a steady magnetic field comparable with the equipartition magnetic field estimate, and Kleeorin et al (2002) demonstrated that a detailed galactic dynamo model based on the equation under discussion gives results very similar to one based on conventional α-quenching. In other words, the real physical description of the nonlinear stage of galactic dynamo is quite complicated but, if we are interested in pragmatic results only, an adequate description can be found by using only a conventional α-quenching.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Kleeorin et al (2000) suggested that a nonlinear galactic dynamo governed by a consistently derived equation for magnetic helicity results in a steady magnetic field comparable with the equipartition magnetic field estimate, and Kleeorin et al (2002) demonstrated that a detailed galactic dynamo model based on the equation under discussion gives results very similar to one based on conventional α-quenching. In other words, the real physical description of the nonlinear stage of galactic dynamo is quite complicated but, if we are interested in pragmatic results only, an adequate description can be found by using only a conventional α-quenching.…”
Section: Introductionmentioning
confidence: 83%
“…We stress that the scenario of Kleeorin et al (2000Kleeorin et al ( , 2002 does not include all possible types of nonlinear processes which can occur at the nonlinear dynamo stage (see, e.g., Brandenburg & Subramanian 2000;Brandenburg & Dobler 2001), but rather is restricted by a minimal number of processes involved in the magnetic helicity conservation. In particular, we consider transport of mean helicity of small-scale magnetic field only and note that this helicity may be transported out of the galactic disc without significant loss of large-scale magnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar effort should be made for stellar dynamos, although there has been, as yet, no progress in this direction. There has been work on the galactic dynamo [47] which incorporates the notion of magnetic helicity current, including the term given in equation (26).…”
Section: Applying and Testing The Theorymentioning
confidence: 99%